PENGARUH AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA SEKOLAH (APBS) TERHADAP PARTISIPASI KOMITE SEKOLAH - Ni Kadek Karmiyanti (Hita Akuntansi dan Keuangan, 2021)
In the world of education, budget management is a plan to supervise finances in the implementation of an activity. Integrated Budget Management between revenue, expenditure and fund management in meeting all the needs needed by schools in improving the quality of education. The source of funds obtained is by charging the overall costs to the parents of students so that there are opportunities for waste and corruption in managing a budget. Therefore, it is necessary to have the participation of the school committee as a supervisor, provide input and consider an activity in the management of the school budget. The purpose of this study is to determine the effect of accountability and transparency of APBS management on school committee participation. The population used in the study was a Swata school in Sukawati sub-district with a total sample size of 38. This study used a saturated sampling method with data analysis techniques used were validity test, reality test, multiple linear regression analysis, determination analysis, F test. and t test. The results of this study state that simultaneously accountability and transparency have a significant effect on participation, with a significant value of the accountability variable of 0.015 <0.05 means that accountability has a positive effect on participation and the transparency variable with a significance value of 0.040 <0.05 means that transparency has a positive effect. Against Participation. So Accountability and Transparency have a positive impact on participation, the greater the value of these variables, the greater can increase school committee participation.